Скінченно-елементний аналіз швидкісного деформування захисних елементів машинобудівних конструкцій - Овчарова, Наталія Юріївна (НТУ "ХПІ", 2017)
Дисертація на здобуття наукового ступеня кандидата технічних наук за спеціальністю 05.02.09 – динаміка та міцність машин. – Національний технічний університет "Харківський політехнічний інститут" Міністерства освіти і науки України, Харків, 2017 В дисертації вирішена актуальна науково-технічна задача визначення динамічного напружено-деформованого стану захисних елементів машинобудівних конструкцій при імпульсному та ударному навантаженнях для забезпечення їх міцності та ефективного використання при експлуатації. На основі тривимірної моделі швидкісного деформування елементів конструкцій, з урахуванням пружно-пластичних скінченних деформацій і динамічних властивостей матеріалів отримані залежності розподілу напружень від швидкості удару за просторовими та часовими координатами в елементах конструкцій. Виявлені нові особливості процесу швидкісного деформування елементів при локальних навантаженнях, що відрізняються визначенням розмірів обмеженої зони напружень з великими градієнтами, утворенням кратерів тощо. Отримані залежності між напруженнями та швидкостями удару в тришаровому елементі для окремих шарів та деформаціями в шарах в залежності від швидкості ударника.

The thesis for a candidate of technical science degree in speciality 05.02.09 – Dynamics and Strength of Machines (engineering sciences) – Kharkov National University "Kharkov Polytechnic Institute", Kharkiv, 2017. In the thesis, the actual scientific and technical problem of determining the dynamic stress-strain state of the protective elements of machine-building structures under impulse and shock loads solved to ensure their strength and effective use during operation. The thesis proposes an improved three-dimensional model of high-rate deformation of structural elements, which is different by taking into account elastic-plastic finite deformations and dynamic properties of materials. Based on the proposed model, the dependences of the distribution of stresses on the speed of impact on spatial and temporal coordinates in structural elements made of various materials obtained. New features of the process of high-rate deformation of elements under local loads detected, differing in the definition of the size of a restricted stress zone with large gradients, the formation of craters and the process of unloading with the appearance of residual stresses and damages. Dependencies between stresses and impact speeds in a three-layer element for individual layers and deformations in layers depending on the speed of the impactor obtained. The dynamic stress-strain state changes significantly both in space coordinates and in time. Therefore, even for thin-walled constructions, the use of the theory of plates and shells is undesirable, since in this case the law of stress distribution over the thickness is preliminarily assumed, and part of the stresses perpendicular to the middle surface are not taken into account at all. The processes of high-speed deformation occur both in the elastic and in the plastic stage and partially accompanied by rather large deformations. Therefore, the work uses three-dimensional models, even for thin-walled structures. From a mathematical point of view, such problems are essentially non-linear and require analysis of a three-dimensional dynamic stress-strain state. The problems of high-rate elastic-plastic deformation of elements of cylindrical structures are considered. It is shown, that the largest displacements and stresses develop in local zones and in the case when the speed is increase up to V ≥ 150 m/s, the area of intense displacements and stresses is R ≤ (10-12) r, where r is the radius of the zone load. These features of the dynamic stress-strain state make it possible to isolate the corresponding region of the element and to make refined calculations for it using a denser grid. A number of practical problems of analyzing the stress-strain state of the elements of the gas turbine engine corps under shock loading considered which differ in the purpose, geometric characteristics and properties of the materials. It is shown, that the largest displacements and stresses develop in bounded zones and rapidly decrease in spatial coordinates both in time and in unloading. It is shown, that when the blade fragment is detached, as well as the foreign particles fall into the flow at the working speeds of the gas turbine engine rotation, the stress intensities do not exceed the prescribed boundaries. In some cases, preference is given to two-layer structures, since they resist shock loads better, than single-layer ones with a larger thickness of the same material.
Finite element analysis of high-rate deformation of protective elements of machine-building structures
Keywords: швидкісне деформування; ударні навантаження; динамічні властивості матеріалів; МСЕ; пружно-пластичні деформації; автореферат дисертації; speed deformation; impact loads; dynamic properties of materials; FEM; elastic-plastic deformation; 539.3